Effect of Culture, Age and Pruning on Mass Production of the VA Mycorrhizal Fungus, Glomus fascicuiatum. - Sreenivasa, M. N; Bagyaraj, D.J (1988)
Glomus fasciculatum .pot cultures were raised in Rhodes grass (Chloris gayana Kunth) using perlite - soilrite mix (1:1 by volume) in 16 cm pots holding 700 g substrate and were harvested at different intervals. Cultures harvested on the 75th day after sowing had the maximum number of infective propagules. In a second experiment, pruning was found to reduce the mychizal propagules up to 4 weeks. However, the propagules increased from 5th week onwards.